The Impact of the Carbon Neutral Era on City Branding and Response Strategies - Lai, Weidong (Business and Economic Research, 2024)
Against the backdrop of increasingly severe global warming, carbon neutrality has become a common goal for all countries, and carbon emission reduction has become an urgent action that all countries and cities need to take. As the center of human activities, cities are the main source of global greenhouse gas emissions, bearing tremendous responsibilities and challenges, and are crucial to promoting carbon neutrality and sustainable development. To achieve the goal of carbon neutrality and sustainable development, more and more cities have adopted various carbon emission reduction strategies to reduce carbon emissions, improve air quality, and enhance the quality of life for citizens. Urban branding is not only a reflection of the image and reputation of the city, but also an important tool for attracting talents, investments, and tourism. As an important component of urban image, urban branding and communication also need to be adjusted and optimized under the background of carbon neutrality era to adapt to and meet the needs of society and citizens. This article aims to explore the strategies and methods of urban branding and communication in the era of carbon neutrality, in order to help cities shape and disseminate competitive and attractive brand images under the carbon neutrality era, and provide suggestions and guidance for relevant urban managers and marketers on urban brand building and development, thereby promoting the sustainable development of urban brands.